Pelas dobras do tempo-espaço: literatura e fotografia em Satolep, de Vitor Ramil - Cimara Valim de Melo (Estudos de Literatura Brasileira Contemporânea)
This paper investigates the relations between time and space in the contemporary literature through the analysis of the novel Satolep, by Vitor Ramil. For that, it views the novel’s cronotopic nature in dialogue with other arts and it also searches material for the study of its symbolic, geographic, social and historic dimensions in relations between the novel and the photography.